HARGA SAHAM PERUSAHAAN MAKANAN DAN MINUMAN PADA BEI DITINJAU DARI KINERJA KEUANGAN TAHUN 2019-2021 - Putu Ayu Putri Padmini; Komang Fridagustina Adnantara; Komang Krishna Yogantara (Universitas Triatma Mulya, 2023)
In 2020, the obtained revenue of Food and Beverage Company merely showed the percentage of 1.8%, in which this revenue indicated an extreme decline compared to 2021 that reached the percentage of 7.9%. This drastic decline was caused by the worldwide outbreak of Covid-19. Thus, both the rise and fall in stock values were influenced by this phenomenon. This study seeks to determine the impact of CR, DER, TATO, and ROA on the stock prices of food and beverage companies listed on the Indonesia Stock Exchange in 2019–2021 in response to the current scenario. For the objectives of this quantitative study, the food and beverage businesses that were listed on the Indonesia Stock Exchange between 2019 and 2021 made up the research population. 60 observations from 20 food and beverage firms were used as a research sample. Purposeful sampling was used to choose the sample. The gathered information was assessed using multiple linear regression. According to the results of the investigation, ROA had a positive impact on stock prices whereas TATO had a negative one. While TATO had a detrimental influence on firm prices, CR and DER had no impact on stock values.